The poetic text in aspect of the linguistic analysis (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2009)
The article deals with the interpretation of the poetic text in linguistic aspect. Акцентируется attention on interaction of figurative-conceptual and language levels of structure of the text. On an example of a linguistic perusal of M. Ryl’sky poetry the role of units of different levels of language in reflection of the ideological and art contents is shown.
Keywords: the linguistic analysis of the text; metro-rhythmic, phonetic, lexical, grammatic levels of the analysis